The Effect of In-store Logistics, Store Image, Sales Promotion, and Service Quality on Customer Satisfaction - Kartika Sari, Yulia; Gani, Ariel Nian (Research of Business and Management, 2024)
This research aims to determine the effect of In-Store Logistics Performance, Store Image, Sales Promotion, and Service Quality on Satisfaction (Case Study of Matahari Department Store Consumers at Artha Gading Mall). The population in this study were consumers of the Matahari Department Store at Artha Gading Mall. The sampling technique used was purposive sampling. The number of respondents in this study was 100 respondents. Data was collected by distributing questionnaires. The data analysis methods used are multiple regression analysis. The results of this research show that: (1) partially In-Store Logistics Performance has a positive effect on consumer satisfaction. (2) Store Image partially has a positive effect on consumer satisfaction. (3) Sales Promotion has a positive effect on consumer satisfaction. (4) Service Quality has a partially positive effect on consumer satisfaction. (5) simultaneously, all independent variables have a positive influence on consumer satisfaction. The managerial implications of these findings are that improving in-store logistics performance, establishing a positive store image, implementing effective sales promotions, and improving service quality can increase customer satisfaction at Matahari Department Store.